In situ synthesis, SHG and luminescent property of a novel acentric 3D-diamond-like zinc tetrazole polymer. (24th November 2015) - Tan, Yu-Hui; Gao, Ji-Xing; Gu, Zhi-Feng; Xu, Qing; Yang, Chang-Shan; Luo, Yan-Sheng; Wang, Bin; Tang, Yun-Zhi; Wen, He-Rui
Graphical abstract: Six neighboring tetrazole groups of different ligands link adjacent six Zn atoms with end to end modes to form a large ring, such building blocks are further linked by other tetrazole groups of ligands through the bridging Zn atoms and extending the structure into a 3D network, the overall structure can be simplified to a 4-c uninodal " dia " network with Schäfli symbol (6, 6). Abstract: The in situ [2+3] cycloaddition reaction of 1, 3-dithiole-2-carbonitrile and NaN3 in the presence of ZnSO4 ·7H2 O, water and ethanol affords a novel 3D-diamond-like networks with diamond subunits as connecting nodes, [(CN4 -C3 H2 S2 )2 Zn] n, (1 ). X-ray diffraction structural analysis reveals that complex1 crystallized in tetragonal crystal system and with I - 42d space group. The second harmonic generation (SHG) measurement reveals that1 is nonlinear optical active with SHG efficiency approximately 0.7 times of the standard potassium dihydrogen phosphate (KDP). Moreover, complex1 exhibits strong blue fluorescent emissions at λ max = 447 nm in the solid state at room temperature.